ANALISIS FAKTOR RESIKO YANG MEMPENGARUHI KARIES GIGI PADA ANAK SD KELAS V-VI DI KELURAHAN PEGUYANGAN KANGIN TAHUN 2015 - Pande Putu Purwaningsih; Ni Made Sirat (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Dental Caries is one of the dental cavity disease as indicated by the damage of the email and dentin layers of the teeth which occurs progressively. The result of the 2013 Riskesdas with comprehensive data collection on dental health including dental health status indicator, service coverage indicators and dental health behaviors where one of the of the age groups being examined are those ≥ 12 years. The objective of the study is to analyze the factors which are related to the caries in elementary school students. The study used cross sectionaldesign being conducted for students of elementary schools as V-VI in the District of Peguyangan Kangin with the sample size of 85 persons. The data analysis used bivariateand multivariate with logistical regression. TheChi-Squareshows that there is a significant relation between oral hygiene and caries with p score = 0,001, OR = 7,714 ,CI 95% =2,064 – 28,828. The teeth brushing behavior influence significantly towards caries with OR score = 20, CI 95% = 5,951 – 69,636 dan p = 0,000 . The behavior in brushing teeth is independentlyand is significant towards caries with score of adjust odd ratio = 18, CI 95% = 4,611 – 74,582 dan p = 0,000 , The dining pattern influences significantly towards caries with OR score = 6, CI 95% = 1,304 – 28,438 and p = 0,012. The parents’ education does not influence significantly towards caries where OR score = 1, CI 95% = 0,486 – 3,854 and p = 0,552and drinking water does not influence significantly towards caries with OR score = 0,753 CI 95% = 0,281 -2,023andp = 0,573. Therefore, it can be concluded that the behavior in brushing teeth, oral hygiene and dining pattern significantly influence dental caries.It is suggested that health care institutions to increase education through UKGS as part of the effort in improving dental health status and oral hygiene of elementary school students.